Globalization and health: Impact pathways and recent evidence - Giovanni Andrea Cornia; Stefano Rosignoli; Luca Tiberti (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
The last two decades of the twentieth century recorded a slowdown in health gains and widespread increases in health inequality across and within countries. The paper explores the causes of such trends on the basis of five main mortality models. To do so, it regresses IMR/LEB on 15 determinants of health. The results underscore the negative health effects of the trends observed between 1980-2000, such as rising inequality, greater income volatility, declining health expenditure, increasing migration and so on. Finally, the paper simulates the level of LEB that would have been achieved in ten regions of the world if the determinants of health had continued developing over these decades as they did over 1960-80. The results indicate that in seven of such regions (including China and India) LEB would have been higher than actually observed. In this regard, the paper raises doubts about the way globalization has taken place and the way public policy oriented it.
Keywords: D63; I18; O15; 330; health status; health inequalities; globalization; Globalisierung; Gesundheit; Sterblichkeit; Welt